Penyelesaian Tindak Pidana Pencurian melalui Denda Adat Antang dan Mekau pada Masyarakat Dayak Bahau di Kampung Keliwai Kabupaten Kutai Barat - Maria Celi Hunyang; La Syarifuddin; Aryo Subroto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This research is motivated by the existence of customary law as a living law that is constitutionally recognized and applied by the Dayak Bahau Community in Keliwai Village in solving the crime of theft. This practice prioritizes local wisdom and social balance through the Antang and Mekau customary fine mechanism as an alternative settlement outside the formal state criminal justice system. However, there are legal issues regarding the effectiveness of sanctions in providing a deterrent effect and protecting the rights of victims, especially vulnerable groups such as people with disabilities. The research uses socio-legal research methods with a qualitative approach through in-depth interviews with traditional chiefs, victims' families, and community leaders. The results of the study show that the implementation of Antang (large urns) and Mekau (small urns) customary fines is carried out through customary deliberations led by the Customary Chief by involving the perpetrators, victims, and families. Philosophically, these fines function as a symbol of